Green Putrajaya / Irfan Khair Salman Khair … [et al.] - Salman Khair, Irfan Khair; Abdul Azis, Qairien Nur Nazihah; Adlin Maryadi, Arfa Irdina; Zulkhairy, Muhammad Zulharraz; Amir, Mohamad Afiq Danish (Faculty of Computer and Mathematical Sciences, 2021)
Green Putrajaya is a mobile application designed to improve the quality of waste management in Putrajaya and to give awareness to the Putrajaya community on the importance of waste management. Around 16,000 tonnes of waste produced by Malaysian on a daily basis, with the number keep increasing from day to day. The same thing happened in Putrajaya where lots of waste was produced in a day which caused illegal dumping. Thus, Green Putrajaya is designed to improve the quality of waste management and to make the community aware of the importance of waste management. Green Putrajaya is built with Putrajaya as a city model as the innovation focuses on the Putrajaya community. The application introduced a Recycle Centre locator for users to easily recycle their rubbish and My Bin for users to schedule their home dustbin waste collection and cleaning with service providers. Also, there are games and videos to give awareness to users on the importance of waste management. This application can be installed in most smartphones and tablets which can give easy access to the community towards proper waste management. Green Putrajaya can be commercialized to all its community since the application can easily be accessed from Google Play. The application can be improved by collaborating the application with other main services like instant delivery and postage which would be more beneficial to the Putrajaya community.